Body Awareness as an Important Target in Multidisciplinary Chronic Pain Treatment: Mediation and Subgroup Analyses. Issue 9 (September 2016) - van der Maas, Lia C.C.; Köke, Albère; Bosscher, Ruud J.; Twisk, Jos W.R.; Janssen, Thomas W.J.; Peters, Madelon
Abstract : Background: The results of a recently performed randomized clinical trial showed that the effect of a multidisciplinary treatment of chronic pain patients on body awareness (BA), catastrophizing, and depression was improved by adding psychomotor therapy (PMT), an intervention targeting BA. No significant effects were found on quality of life and disability. The present follow-up study aimed to explore the relationship between improvements in BA and multidisciplinary chronic pain rehabilitation treatment outcome across treatment conditions and the possible mediating effect of BA between treatment conditions. Furthermore, the hypothesis that patients with low BA benefit more from PMT was investigated. Methods: In total, 94 patients with chronic pain participated in a randomized clinical trial comparing multidisciplinary treatment as usual (TAU) with TAU plus PMT. Outcome variables were health-related quality of life, disability, and depression. Self-efficacy and catastrophizing were the process variables of treatment and the potential mediating factors in the relationship between BA and the outcome variables. The data were analyzed by linear mixed-model analysis. Results: Improvements in BA were related to improvements in all outcome variables across treatment conditions. The relationships were partly mediated by self-efficacy, catastrophizing, or both. In the regression model with depression as the outcome variable, the regression coefficient of treatment (ie, PMT vs. TAU) decreased by 34% and became nonsignificant when BA was added as a potential mediator. Patients with low BA seemed to benefit more from PMT than patients with high BA, especially on depression, BA, and catastrophizing. Conclusions: BA might be an important target of treatment to improve the multidisciplinary treatment outcome in chronic pain patients. Furthermore, PMT is an intervention that seems to provide its benefits through improving BA and may be especially beneficial for patients with low BA.